The Effect of Ratio of Lemongrass Stalk Juice with Galingale Juice and Concentration of Palm Sugar Powder on the Quality of Lemongrass Fresh Drink Powder - Tio Maria Situmorang; Rona J. Nainggolan; Herla Rusmarilin (Jurnal Rekayasa Pangan dan Pertanian, 2015)
This research was conducted to determine the effect of ratio of lemongrass stalk juice with galingale juice and concentration of palm sugar powder on the quality of lemongrass fresh drink powder . This research was conducted using completely randomized design (CRD) with, two factors i.e : ratio of lemongrass stalk juice with galingale juice (S) : (95% : 5, 90% : 10% , 85% : 15%, 80% : 20%) and concentration of palm sugar powder (G) : (12%, 14%, 16%, 18%). The parameters analyzed were moisture content, ash content, total acid, total soluble solid, solubility, the score value of color and taste, and the hedonic value of flavor and taste. The results showed that of lemongrass stalk juice with galingale juice had highly significant effect on moisture content, and flavor. Concentration of palm sugar powder had highly significant effect on moisture content, ash content, total acid, total soluble solid, solubility, score of color and taste, the hedonic value of taste. The interaction between the two factors had significant effect on taste. Ratio of lemongrass stalk juice with galingale juice of 90% : 10% and concentration of palm sugar powder of 18% produced the best quality of lemongrass fresh drink powder . Keywords : Galingale, lemongrass, lemongrass stalk juice, palm sugar, powder.